Targeting Inflammation in the Diagnosis, Management, and Prevention of Cardiovascular Diseases - Akira Matsumori (Ubiquity Press, 2022)
Inflammation plays an important role in the development and progression of cardiovascular diseases (CVDs). Hypertension and hyperlipidemia are the key risk factors of CVDs and induce inflammation in the heart and vessels. Unhealthy diet, infection, and smoking coupled with genetic factors lead to the development of CVDs as well as induce inflammation. Risk factors of CVDs such as hypertension and hyperlipidemia along with diabetes activate nuclear factor kappa B, which regulates the transcription of immunoglobulin free light chain (FLC) κ in B cells and the production of multiple inflammatory molecules, leading to inflammation. FLCs are novel biomarkers of inflammation, and their levels have been associated with overall mortality in a general population and with cardiovascular outcomes. In this review, the role of inflammation in the pathogenesis of CVDs, new biomarkers of inflammation, and dietary options counterbalancing inflammatory processes, such as the polyphenol-rich French maritime pine bark extract Pycnogenol, are discussed.